2019
DOI: 10.24059/olj.v13i4.1646
|View full text |Cite
|
Sign up to set email alerts
|

Is the Whole Greater Than the Sum of Its Parts? A Comparison of Small Group and Whole Class Discussion Board Activity in Online Courses

Abstract: Methods for characterizing asynchronous text-based discussions have received significant attention in the literature. In this study, we examine student and instructor posts made in seventeen undergraduate mathematics courses over the duration of a fifteen-week semester (n=6964 posts). We apply our previously developed multifactor discussion board metric to compare differences in student participation, quantities of student posts, quality of posts, extent of threading, and instructor presence in small group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
2
7
0
2
Order By: Relevance
“…Based on the results of the research obtained from the average posttest 85.81 for the experimental class and 72.43 for the control class, it showed that the improvement of the students' learning outcomes in the experimental class using whole-group discussion is better than the control class using learning buzz-group discussion, this is in accordance with opinion [4] Rather than look at small group and whole class discussions in different courses or singles courses (as in a case study), we measured differences in the same learners grouped in whole class and small groups. The results of this study support some claims that small group activities afford such benefitsas increased student participation, peer interactions and the development of socially constructed knowledge.…”
Section: Discussionsupporting
confidence: 64%
“…Based on the results of the research obtained from the average posttest 85.81 for the experimental class and 72.43 for the control class, it showed that the improvement of the students' learning outcomes in the experimental class using whole-group discussion is better than the control class using learning buzz-group discussion, this is in accordance with opinion [4] Rather than look at small group and whole class discussions in different courses or singles courses (as in a case study), we measured differences in the same learners grouped in whole class and small groups. The results of this study support some claims that small group activities afford such benefitsas increased student participation, peer interactions and the development of socially constructed knowledge.…”
Section: Discussionsupporting
confidence: 64%
“…For instance, Bernard et al (2009) highlighted student-to-student interaction as one of three interaction types that can increase student engagement in online courses. Research has also found that online collaboration tools can enhance students' sense of community (Dawson, 2006), increase the knowledge flow between students (Bliss & Lawrence, 2009), and encourage overall participation (Bliss & Lawrence, 2009;Hrastinski, 2006). Online collaboration additionally leaves behind data traces which can be used to develop and evaluate effective teacher interventions (van Leeuwen, Janssen, Erkens, & Brekelmans, 2014).…”
Section: Participation Variations In Csclmentioning
confidence: 99%
“…Computer-supported collaborative learning (CSCL) has been found to positively support students' learning by increasing knowledge exchanges (Bliss & Lawrence, 2009;Resta & Laferrière, 2007;Schellens & Valcke, 2005) and encouraging connections between students (Bernard et al, 2009;Dawson, 2006). Yet, recent research has also demonstrated wide variations in participation levels between students (Caspi, Gorsky, & Chajut, 2003;Hämäläinen & Arvaja, 2009;Strijbos & de Laat, 2010;Wise, Perera, Hsiao, Speer, & Marbouti, 2012), which ultimately hinder the collaboration experience.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, researchers and practitioners need a way to better understand how active instructors are in a course. One method was created by Bliss and Lawrence ( 2009a , b ). In this method, the calculation of instructor participation is the total number of instructor posts divided by the number of students in the course.…”
Section: Resultsmentioning
confidence: 99%